Moringa Oleifera Extract Decreases Interleukin 6 Levels and Disease Activity in Rheumatoid Arthritis Patients (Bangladesh Journal of Medical Science, 2023)
Moringa oleifera (MO) has anti-inflammatory, anti-arthritis, and immunosuppressant effects in Rheumatoid Arthritis (RA). This study aims to determine the effect of moringa oleifera extract on interleukin 6 levels and disease activity in RA. This research, with 30 patients, was divided into two groups: the intervention and the placebo. The intervention group received 40.50 mg/kg BW/day of Moringa oleifera extract for one month. IL-6 levels and SDAI scores were measured before and after the treatment. Paired t-test showed that IL-6 levels (p=0.070) and SDAI Scores (p=0.142) before and after MO administration for the control group were not significantly different (p> 0.05). Paired t-test IL-6 (p=0.001) and SDAI Scores (p=0.001) before and after giving MO to the treatment group decreased significantly (p